A total internal reflection-fluorescence correlation spectroscopy setup with pulsed diode laser excitation - Weger, Lukas; Hoffmann-Jacobsen, Kerstin (Review of scientific instruments, 2017)
Fluorescence correlation spectroscopy (FCS) measures fluctuations in a (sub-)femtoliter volume to analyze the diffusive behavior of fluorescent particles. This highly sensitive method has proven to be useful for the analysis of dynamic biological systems as well as in chemistry, physics, and material sciences. It is routinely performed with commercial fluorescence microscopes, which provide a confined observation volume by the confocal technique. The evanescent wave of total internal reflectance (TIR) is used in home-built systems to permit a surface sensitive FCS analysis. We present a combined confocal and TIR-FCS setup which uses economic low-power pulsed diode lasers for excitation. Excitation and detection are coupled to time-correlated photon counting hardware. This allows simultaneous fluorescence lifetime and FCS measurements in a surface-sensitive mode. Moreover, the setup supports fluorescence lifetime correlation spectroscopy at surfaces. The excitation can be easily switched between TIR and epi-illumination to compare the surface properties with those in liquid bulk. The capabilities of the presented setup are demonstrated by measuring the diffusion coefficients of a free dye molecule, a labeled polyethylene glycol, and a fluorescent nanoparticle in confocal as well as in TIR-FCS.